PERAN KANTOR URUSAN AGAMA SANGATTA UTARA DALAM MEMINIMALISIR PERCERAIAN DI PENGADILAN AGAMA SANGATTA - Ajis Supangat; Linda Auliana (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
The purpose of this research is to describe the causes of divorce, the role of the religious affairs office in minimizing divorce, and the considerations of judges in making decisions. the method used in this research is a qualitative research method with a type of field research. The results concluded that several factors cause divorce including economic factors, domestic violence (KDRT), and infidelity, as for the way to minimize divorce is to organize socialization by the North Sangatta Religious Affairs Office regarding understanding knowledge in married life. The judge's considerations in making a decision are accepting and granting the plaintiff's claim in its entirety, giving permission to the plaintiff to impose a divorce of one raji'i against the defendant, charging case costs to the plaintiff or if the court is of another opinion, the plaintiff requests the fairest decision.